Little secrets - Hillier, Jennifer (Minotaur Books, 2020)
"All it takes to unravel a life is one little secret... Marin had the perfect life. Married to her college sweetheart, she owns a chain of upscale hair salons, and Derek runs his own company. They're admired in their community and are a loving family - until their world falls apart the day their son Sebastian is taken. A year later, Marin is a shadow of herself. The FBI search has gone cold. The publicity has faded. She and her husband rarely speak. She hires a P.I. to pick up where the police left off, but instead of finding Sebastian, she learns that Derek is having an affair with a younger woman. This discovery sparks Marin back to life. She's lost her son; she's not about to lose her husband, too. Kenzie is an enemy with a face, which means this is a problem Marin can fix. Permanently."--Provided by publisher.